Bacteriorhodopsin: Would the real structural intermediates please stand up? - Wickstrand, Cecilia; Dods, Robert; Royant, Antoine; Neutze, Richard (Biochimica et biophysica acta, 2015)
Bacteriorhodopsin (bR) is the simplest known light driven proton pump and has been heavily studied using structural methods: eighty four X-ray diffraction, six electron diffraction and three NMR structures of bR are deposited within the protein data bank. Twenty one X-ray structures report light induced structural changes and changes induced by mutation, changes in pH, thermal annealing or X-ray induced photo-reduction have also been examined. We argue that light-induced structural changes that are replicated across several studies by independent research groups are those most likely to represent what is happening in reality. We present both internal distance matrix analyses that sort deposited bR structures into hierarchal trees, and difference Fourier analysis of deposited X-ray diffraction data. An internal distance matrix analysis separates most wild-type bR structures according to their different crystal forms, indicating how the protein's structure is influenced by crystallization conditions. A similar analysis clusters eleven studies of illuminated bR crystals as one branch of a hierarchal tree with reproducible movements of the extracellular portion of helix C towards helix G, and of the cytoplasmic portion of helix F away from helices A, B and G. All crystallographic data deposited for illuminated crystals show negative difference density on a water molecule (Wat402) that forms H-bonds to the retinal Schiff Base and two aspartate residues (Asp85, Asp212) in the bR resting state. Other recurring difference density features indicated reproducible side-chain, backbone and water molecule displacements. X-ray induced radiation damage also disorders Wat402 but acts via cleaving the head-groups of Asp85 and Asp212. A remarkable level of agreement exists when deposited structures and crystallographic observations are viewed as a whole. From this agreement a unified picture of the structural mechanism of light-induced proton pumping by bR emerges. This article is part of a Special Issue entitled Structural biochemistry and biophysics of membrane proteins. [Display omitted] •A hierarchal tree for all pdb entries of wild type bacteriorhodopsin (bR)•A hierarchal tree for all pdb entries describing bR intermediates•Difference Fourier maps from all bR intermediates with crystallographic data•A unified view of the structural mechanism of proton pumping by bR.